ANALYSIS OF DIGITALIZATION OF OUTPATIENT SERVICES FOR BPJS HEALTH PATIENTS AT JOMBANG REGIONAL PUBLIC HOSPITAL - Sangidu; Peristiowati, Yuly; Anggraini, Novita Ana (International Journal of Cultural and Social Science, 2026)
The digitalization of healthcare services is a key strategy to improve service quality, efficiency, and accessibility, particularly for patients covered by Indonesia's National Health Insurance (BPJS Kesehatan). Jombang Regional General Hospital (RSUD Jombang) has implemented digital systems in outpatient services; however, various challenges hinder optimal service delivery. This study aims to analyze the implementation of digitalization, identify technical and non-technical barriers, and explore the expectations of healthcare staff and patients regarding its development. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with registration staff, healthcare providers in cardiology and general surgery outpatient clinics, and BPJS Kesehatan patients at RSUD Jombang. Data analysis was conducted using NVivo 12 software, utilizing thematic analysis and source triangulation. The implementation of digitalization includes online registration, digital queuing systems, integration between the Hospital Management Information System (SIMRS) and BPJS Kesehatan, and the use of Electronic Medical Records (EMR), contributing to improved time efficiency and ease of access. However, technical barriers such as unstable network connectivity and limited infrastructure were identified, along with non-technical barriers including disparities in digital literacy among staff and patients (especially the elderly). Both healthcare providers and patients expressed expectations for more stable systems, more supportive features, and more user-friendly designs.